Forming of plates and disks samples from austenitic stainless steel, manganese carbon steel and low carbon steel using laser heating - O. Kaglyak; A. Lutay; O. Goncharuk; L. Golovko (Mechanics and Advanced Technologies, 2018)
The aim of research was investigate possibility and specific of laser forming of austenitic stainless steel and manganese carbon steel, make results comparison between specimens treated by pressure and laser formed specimens. In this research the mechanisms of laser forming were analyzed. Thermal gradient mechanism (TGM) is the most suitable and the most effective. The recommendation of treatment condition based on results of experimental investigation presented in this paper. The value of deformation was proportional to the number of scans and inversely proportional to the scanning speed for both carbon and stainless steel specimens. While treating carbon steel the effect of ‘post deformation’ can occur, it does can have the direction, which matches with the direction of main deformation or can be opposite. This effect can be explained by polymorphic transformation which occurs in carbon steels during heating-cooling cycle. Stability of laser formed designs was under investigation. Was found, that during laser forming of discs, to achieve uniform deformation, should use uniform heating conditions created by closed circuit heating area.